The Implementation of Hardship Principles in OJK Regulation Number 11/POJK.03/2020 as a Strategy of Economic Strengthening in Handling the Impact of COVID-19 Pandemic - Antryo Sandra Dewi; Arief Suryono; Yudho Taruno Muryanto (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
This legal research examines the implementation of the principle of hardship in the economic stimulus policies issued by the Government of Indonesia as a strategy to strengthen the economy in handling with the impact of the COVID-19 pandemic. This legal research is a normative or doctrinal legal research conducted by reviewing the literature. The research approach carried out uses a statue approach and a conceptual approach. This legal research uses both primary and secondary legal materials. Based on the results of this legal research, the implementation of the hardship principle which has different implications from the forje majeur or overmacht principle is considered to be able to accommodate the interests and legal protection of the rights of creditors and debtors. The principle of hardship become a legal basis for not canceling a contract so as to maintain the continuity of the contract. The application of the principle of hardship in Financial Service Authority in Indonesia it called as “Otoritas Jasa Keuangan” (OJK) Regulation Number 11 / POJK.03 / 2020 aims to achieve justice for debtors and creditors in the context of facing conditions of decline in economic growth due to the impact of COVID-19 pandemic. Keywords: principles of hardship; economic stimulus policy; COVID-19 pandemic